The Degree to Which Parents Practice the Method of Dialogue and Discussion Included in Islamic Educational Thought from The Children’s Point of View - Al-rosan, Nusaiba Dyab Mohammad; AL-Momani, Mohammad Omar; Rababah, Basma Ali Ahmed; ALOBAIDAT, BATOOl MOHAMMAD MAJED; DIABAT, DIYA’ WALEED KHALAF (Journal of Ecohumanism, 2025)
The study aimed to identify the degree to which parents practice the method of dialogue and discussion included in Islamic educational thought from the children’s point of view and the relationship of this to some variables such as gender, academic specialization, and stage of study. The researcher followed the descriptive analytical approach by applying a questionnaire consisting of (14) items, which served as a tool. For the study, which was applied to (2500) male and female students from various Jordanian universities in the second semester of the academic year (2023/2024), the study concluded, after conducting appropriate statistical treatments, that the level of parents’ practice of the method of dialogue and discussion included in Islamic educational thought is generally In general, it was scored (high) on the scale as a whole, with an arithmetic mean of (3.89) and a standard deviation of (0.63). The results also revealed that there were no statistically significant differences attributable to the variables of the study, namely the variables of gender (males, females) and the variable of the type of student’s academic specialization (scientific, Humanitarian) and the variable of the student’s academic stage (intermediate diploma, bachelor’s degree).